2021
DOI: 10.3390/metabo11090628
|View full text |Cite
|
Sign up to set email alerts
|

A Distinctive Human Metabolomics Alteration Associated with Osteopenic and Osteoporotic Patients

Abstract: Osteoporosis is a common progressive metabolic bone disease resulting in decreased bone mineral density (BMD) and a subsequent increase in fracture risk. The known bone markers are not sensitive and specific enough to reflect the balance in the bone metabolism. Finding a metabolomics-based biomarker specific for bone desorption or lack of bone formation is crucial for predicting bone health earlier. This study aimed to investigate patients’ metabolomic profiles with low BMD (LBMD), including those with osteope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…Strong logical and biochemical interaction seasonalized the occurrence of these three elements. The pathway analysis in Figure S7 echoes with the conclusion of inflammation by disorders including phenylalanine metabolism, histidine metabolism, purine metabolism, which are closely related to inflammation 44,45,51 . At the same time, the reduction of carnosine and anserine level provide absent of anti-oxidative process, where oxidative stress is aggravated and the risk of necrosis was hastened.…”
Section: Untargeted Metabolomic Profiling Analysismentioning
confidence: 52%
See 1 more Smart Citation
“…Strong logical and biochemical interaction seasonalized the occurrence of these three elements. The pathway analysis in Figure S7 echoes with the conclusion of inflammation by disorders including phenylalanine metabolism, histidine metabolism, purine metabolism, which are closely related to inflammation 44,45,51 . At the same time, the reduction of carnosine and anserine level provide absent of anti-oxidative process, where oxidative stress is aggravated and the risk of necrosis was hastened.…”
Section: Untargeted Metabolomic Profiling Analysismentioning
confidence: 52%
“…Main pathway disorders included phenylalanine metabolism, histidine metabolism, purine metabolism. It had been reported that these pathways are related with OP not only in bone tissue but also in blood 44,45 . Our study has provided the analyses by combining untargeted and targeted metabolomics to prove the disturbance of muscle metabolism by OP disease in early stage, where severe and obvious muscle dysfunction have not occurred.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently dysregulated metabolic pathways in low bone mineral density included histidine metabolism, glyoxylate, aminoacyl-tRNA biosynthesis, dicarboxylate metabolism and unsaturated fatty acid biosynthesis. Additional analyses revealed differences between patients with osteopenia and osteoporosis, including different levels of carboxy-4-methyl-5-propyl-2-2furanopropionic acid, carnitine derivatives, phosphatidylcholine, sphingomyelin and palmitic acid [ 32 ].…”
Section: Osteoporosismentioning
confidence: 99%
“…The reason why recent studies have focused on the role of metabolic abnormalities in Osteoporotic OA is precisely due to the similarities in the loss of bone homeostasis between OP and OA (8). Studies have shown that under high body mass index, excessive adipokines release and metabolic changes lead to the occurrence of OP and increased fracture risk (9)(10)(11). It is well known that a high body mass index not only brings more mechanical load to OA by increasing body weight but also increases the risk of OA by inducing sterile inflammation through adipokines (12).…”
Section: Introductionmentioning
confidence: 99%